Chemical Diversity in the G Protein-Coupled Receptor Superfamily. (May 2018) - Vass, Márton; Kooistra, Albert J.; Yang, Dehua; Stevens, Raymond C.; Wang, Ming-Wei; de Graaf, Chris
Abstract : G protein-coupled receptors (GPCRs) are the largest family of cell signaling transmembrane proteins that can be modulated by a plethora of chemical compounds. Systematic cheminformatics analysis of structurally and pharmacologically characterized GPCR ligands shows that cocrystallized GPCR ligands cover a significant part of chemical ligand space, despite their limited number. Many GPCR ligands and substructures interact with multiple receptors, providing a basis for polypharmacological ligand design. Experimentally determined GPCR structures represent a variety of binding sites and receptor–ligand interactions that can be translated to chemically similar ligands for which structural data are lacking. This integration of structural, pharmacological, and chemical information on GPCR–ligand interactions enables the extension of the structural GPCR–ligand interactome and the structure-based design of novel modulators of GPCR function. Highlights: The structural coverage of chemical GPCR ligand space can be efficiently extended by systematic structural cheminformatics analyses. The integration of GPCR bioactivity data, structural receptor–ligand interaction analyses, and chemical similarity searches yields a comparative map of the pharmacological and structural GPCR–ligand interactome. The systematic analysis of multitarget ligands and ligand substructures as well as receptor binding site similarities provides insights into opportunities and limitations for the identification and design of polypharmacological GPCR ligands. The combination of GPCR bioactivity data mining, structural receptor–ligand interaction analyses, molecular similarity assessments, and chemical scaffold evaluations offers building blocks for the construction of a structure-based GPCR medicinal chemistry toolbox.